Morfologia de ovos de Dioctophyme renale Goeze, 1782 (Nematoda: Dioctophymatidae) e influência da temperatura no desenvolvimento de larvas de primeiro estágio nos ovos - Pedrassani, Daniela [UNESP] (2009)
This study aims to provide information on morphological data of D. renale eggs, as well as on first-stage larvae development into eggs kept at different temperatures. Eggs were obtained by centrifugation of infected dog urine, placed in Petri dishes, and stored in BOD chamber for a 90-day period. Each treatment (GI - 15 °C, GII - 20 °C, and GIII - 26 °C) was repeated fve times. Eggs showed average measures of 67.23 × 42.78 μm, and the mean incubation time was inversely proportional to the incubation temperature. Larvae motility was observed one week after being observed in eggs.